Use of the conditional marketing authorization pathway for oncology medicines in Europe - Hoekman, J; Boon, W P C; Bouvy, J C; Ebbers, H C; de Jong, J P; De Bruin, M L (Clinical pharmacology and therapeutics, 2015)
Conditional marketing authorization (CMA) in the European Union (EU) is an early access pathway for medicines that show promising therapeutic effects, but for which comprehensive data are not available. Using a mixed quantitative-qualitative research design, we evaluated how CMA has been used in marketing authorization of oncology medicines in the period 2006 to 2013. We show that compared to full marketing authorization, CMA is granted based on less comprehensive data. However, this is accompanied by significantly longer assessment times and less consensus among regulators about marketing authorization. Moreover, development time from first-in-human testing to marketing authorization did not differ between full marketing authorization and CMA, but was significantly longer for CMA compared to accelerated approved products in the United States (US). Results indicate that CMA is not used by companies as a prospectively planned pathway to obtain early access, but as a "rescue option" when submitted data are not strong enough to justify full marketing authorization.